Pancreatic islet transplantation: current advances and challenges - Wang, Qi; Huang, Yu-xi; Liu, Long; Zhao, Xiao-hong; Sun, Yi; Mao, Xinli; Li, Shao-wei (Frontiers in Immunology, 2024)
Diabetes is a prevalent chronic disease that traditionally requires severe reliance on medication for treatment. Oral medication and exogenous insulin can only temporarily maintain blood glucose levels and do not cure the disease. Most patients need life-long injections of exogenous insulin. In recent years, advances in islet transplantation have significantly advanced the treatment of diabetes, allowing patients to discontinue exogenous insulin and avoid complications.Long-term follow-up results from recent reports on islet transplantation suggest that they provide significant therapeutic benefit although patients still require immunotherapy, suggesting the importance of future transplantation strategies.Although organ shortage remains the primary obstacle for the development of islet transplantation, new sources of islet cells, such as stem cells and porcine islet cells, have been proposed, and are gradually being incorporated into clinical research. Further research on new transplantation sites, such as the subcutaneous space and mesenteric fat, may eventually replace the traditional portal vein intra-islet cell infusion. Additionally, the immunological rejection reaction in islet transplantation will be resolved through the combined application of immunosuppressant agents, islet encapsulation technology, and the most promising mesenchymal stem cells/regulatory T cell and islet cell combined transplantation cell therapy. This review summarizes the progress achieved in islet transplantation, and discusses the research progress and potential solutions to the challenges faced.